Preparation, synthesis and characterizations of La0.7Sr0.3Mn(1-y)Ni(y)O3 alloy - Setiawan, Jan; Susetyo, Ferry Budhi; Nanto, Dwi; Simbolon, Silviana; Notonegoro, Hamdan Akbar; Al Farizi, Taufiq; Yunasfi; Tihera, Dinda; Ramlan (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
Nickel (Ni) doped in the perovskite manganite could result in superior properties. The effect of the Ni on the morphology, crystallographic orientation, and magnetic properties of La0.7Sr0.3Mn(1-y)Ni(y)O3 alloy (y = 0.1, 0.3, 0.5, and 0.7), therefore, was undertaken. La0.7Sr0.3Mn(1-y)Ni(y)O3 alloy was firstly processed using a ball milling process, and again processed through heat treatment and crushing at the end of the synthesis process. Powder alloy was then investigated using a scanning electron microscope equipped with scanning electron microscope and energy dispersive spectroscopy (SEM-EDS), x-ray diffraction (XRD), and vibrating sample magnetometer (VSM). The particle size became smaller and agglomerated as the amount of Ni doping increased. The polycrystal structure phase formed would become more complex when the Ni doping was 0.5 and 0.7, where the dominant phase formed was La2NiO4 even though the La0.7Sr0.3Mn(1-y)Ni(y)O3 phase was still formed. The magnetic characteristics showed that the Ni doping of 0.1 had a higher magnetization value around 4.2 emu/g at room temperature.